Building Faculty Community via OER - Jorg Waltje; Amanda Zerangue (Academic Chairpersons Conference Proceedings, 2020)
This presentation will delineate ways for chairs and college administrators to encourage faculty to explore better and less costly ways to deliver instructional content to their students. It will highlight how to reward and recognize these efforts, while at the same time creating excellent opportunities for faculty collaborations and community building.
Keywords: Faculty Development; Faculty Collaboration; OER; Accessibility; Inclusiveness; Student Outcomes; Overcoming Financial Barriers to HE